If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -96 = 69 + -6 + -2x Combine like terms: 69 + -6 = 63 -96 = 63 + -2x Solving -96 = 63 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -96 + 2x = 63 + -2x + 2x Combine like terms: -2x + 2x = 0 -96 + 2x = 63 + 0 -96 + 2x = 63 Add '96' to each side of the equation. -96 + 96 + 2x = 63 + 96 Combine like terms: -96 + 96 = 0 0 + 2x = 63 + 96 2x = 63 + 96 Combine like terms: 63 + 96 = 159 2x = 159 Divide each side by '2'. x = 79.5 Simplifying x = 79.5
| y=8+2x^2-x^4 | | -104=-4(-4k-2) | | 6d+8d+7d-4= | | -104=-(-4k-2) | | -104=-4(4k-2) | | 7x-112=2x-7 | | -15x-5=7 | | 8y+5y+4y-7= | | 230=-8-7(6x+2) | | .2x-7=6.8 | | (3*x)+(2*y)=375 | | 5(2n+3)=8(4n+9)+6 | | -5(1-6v)=175 | | 5x-1+4(x-3)=(3x-2)-3(x+2) | | 18x-8=4(3x-3)+6x+4 | | -10=-14v+10v | | 400-.03x=X | | 6x-2(4x-5)=46 | | -4(w-6)+7=-33 | | x-0.7=1.6 | | Y-5/2=1/2 | | 3(6+7n)=102 | | 5(3x+5)=12 | | -7(-2-2x)=-84 | | 2(3x+4x)=14 | | 194=6(5n+4)+4n | | X-08/8/9=6/7 | | -2(4t-4)+5t=6t-9 | | -5(-4-2m)=90 | | -4(3y-2)-y=-3(y-3) | | gh2j/s | | 9x+0.3=63.3 |